2021
DOI: 10.33545/26174693.2021.v5.i1a.64
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of HBA1C & superoxide dismutase in type II diabetes mellitus in Jalgaon district

Abstract: Type II diabetes formerly known as adult-onset diabetes, is a type of diabetes that is characterized by high blood sugar, insulin resistance, and relative lack of insulin due to obesity, lack of exercise or genetically determined. HbA1c in diabetic patients provides valuable information about the changes occurring in the blood glucose level over last three months. SOD is considered as a first line Defense against ROS, as it is present in almost all cells and it deals with the most hazardous radicals i.e. Super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As a metabolic disorder, diabetes is associated with increased levels of free radicals and decreased activity of antioxidants, and some studies have suggested that increased oxidative stress in diabetes may be due to increased formation of glycosylated hemoglobin. The increase in the formation of glycosylated hemoglobin develops diabetes and its consequences (14). Researchers have shown that regular exercise leads to a decrease in glycosylated hemoglobin levels (15).…”
Section: Introductionmentioning
confidence: 99%
“…As a metabolic disorder, diabetes is associated with increased levels of free radicals and decreased activity of antioxidants, and some studies have suggested that increased oxidative stress in diabetes may be due to increased formation of glycosylated hemoglobin. The increase in the formation of glycosylated hemoglobin develops diabetes and its consequences (14). Researchers have shown that regular exercise leads to a decrease in glycosylated hemoglobin levels (15).…”
Section: Introductionmentioning
confidence: 99%